Pengaruh tingkat partisipasi angkatan kerja, indeks harga konsumen, produk domestik regional bruto terhadap upah rata-rata Pulau Sumatera - Dearni Christina Purba; Purwaka Hari Prihanto; Siti Aminah (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2020)
This study ains to analyze the Development of Labor Force Participation Rate, Consumer Price Index and Gross Regional Domestic Product and Average Wages in Sumatera and analyze the influence of the Development of Labor Force Participation Rate, Consumer Price Index, and Gross Regional Domestic Product on Average Wages in Sumatera. The data used in this study are secondary data sourced from the Central Statistics Indonesia office. For data analysis using panel data analysis. The average wage is a Bound variable that is influenced by three independent variables, namely the Labor Force Participation Rate, the Consumer Price Index, and the Gross Regional Domestic Product. Based on the result of the analysis it is known that the Labor Force Participation Rate has a negative and not significant effect on the average wage in Sumatera. The consumer Price Index has a negative and not significant effect on the average wages in Sumatera. Gross Regional Domestic Product has a positive and significant effect on Average Wages in Sumatera.